2022
DOI: 10.3389/fphar.2022.919181
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiota-derived metabolites in inflammatory diseases based on targeted metabolomics

Abstract: The gut microbiota plays an important role in inflammatory diseases. Metabolites in the three metabolic pathways of tryptophan (Trp), histidine (His), and phenylalanine (Phe) can affect various inflammatory conditions, such as obesity, diabetes, arthritis, colitis, atherosclerosis, and neuroinflammation. We established an LC–MS/MS method to measure 17 metabolites—Trp, 3-indole-acetic acid (Iaa), 3-indole-lactate (Ila), 3-indole-propionic acid (Ipa), 3-indole formaldehyde (Iald), kynurenine (Kn), kynurenic acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 62 publications
0
16
0
Order By: Relevance
“…Small metabolites are transported into the bloodstream via transcellular or paracellular routes, whereas large metabolites disrupt the gut barrier and are released into the body ( Kirichenko et al, 2020 ). Indole derivatives, such as indoxyl sulfate, indole ethanol, and indole acrylic acid, are produced by the gut microbiota from tryptophan and induce proinflammatory activity after entering the bloodstream ( Xu H et al, 2022 ). In addition, indolepropionic acid (IPA), which is metabolized from tryptophan, is substantially reduced in patients with coronary artery disease.…”
Section: Gut Microbiota Disorders Target Mitochondria and Are Closely...mentioning
confidence: 99%
“…Small metabolites are transported into the bloodstream via transcellular or paracellular routes, whereas large metabolites disrupt the gut barrier and are released into the body ( Kirichenko et al, 2020 ). Indole derivatives, such as indoxyl sulfate, indole ethanol, and indole acrylic acid, are produced by the gut microbiota from tryptophan and induce proinflammatory activity after entering the bloodstream ( Xu H et al, 2022 ). In addition, indolepropionic acid (IPA), which is metabolized from tryptophan, is substantially reduced in patients with coronary artery disease.…”
Section: Gut Microbiota Disorders Target Mitochondria and Are Closely...mentioning
confidence: 99%
“…3-MH, as a part of the histidine metabolic pathway, may have a role in inflammation diseases. However, the association was not established in stool on a mice model 53 . An in vivo study analyzing feces has recently found lower amounts of 3-MH and anserine ( see section 3.2.2 ) in patients with irritable bowel syndrome 56 .…”
Section: Results and Discusionmentioning
confidence: 93%
“…Higher levels of tyrosine (Fig 3, C) and tryptophan (Fig 3, D) were observed in the PP than in the rest of the groups throughout the colonic fermentation. Phenylalanine, tryptophan, and histidine metabolomic pathways are closely related to gut inflammation 53 . In the case of phenylalanine and tryptophan, no relevant derived metabolites were found through the metabolomics pipeline.…”
Section: Results and Discusionmentioning
confidence: 99%
“…Furhermore, the inflammatory and metabolic pathways are complex networks contextdependent by various factors, including genetics, diet, cell status, and environmental factors (Yang et al, 2022). The mechanism of gut microbiota involvement in the occurrence and development of inflammatory diseases is very complex, and research on how intestinal metabolites and the host interact to affect diseases is a hot topic (Xu et al, 2022a). Further studies are needed to assess the impact of intestinal dysbiosis and gut microbiota-derived metabolites rather than specific bacterial species to understand the mechanisms involved in RA pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Growing evidence has suggested the role of gut microbiota in the onset of arthritis. Studies in mice (Rosser et al, 2014;Liu et al, 2016;Jubair et al, 2018;Maeda and Takeda, 2019;Peng et al, 2019;Aa et al, 2020), rats (Huang et al, 2019;Peng et al, 2019;Yue et al, 2019;Xu et al, 2020;Xu et al, 2022a), and pigs (Mansson et al, 1971) consistently demonstrate that gut dysbiosis is associated with inflammatory arthritis development.…”
Section: Introductionmentioning
confidence: 99%